1994
DOI: 10.1111/j.1365-2249.1994.tb06571.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological and clinical significance of neutralizing and binding antibodies to interferon-alpha (IFN–α) during therapy for chronic hepatitis C

Abstract: SUMMARYIt is known that IFN therapy can induce the development of anti-IFN antibodies. In order to evaluate the biological and clinical significance of both neutralizing (NA) and non-neutralizing (binding) antibodies, 123 patients with chronic hepatitis C treated with recombinant IFN-fi were examined. Among them. 15 were positive for NA and 24 for binding antibodies. The kinetics of NA appearance show that, in general, they develop early during the first 3 months of treatment. Moreover. NA seem to be clinicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…demonstrated that Ab production is low and not hampering treatment responses to PEG‐IFN. Furthermore, these results are also supported by earlier studies showing no significant differences in overall percentage of sero‐conversion between responders and non‐responders. The differences in AST but not ALT levels found here are also in agreement with a recent report showing that rapid normalization of ALT by 4 weeks after treatment might be an independent significant predictive factor for SVR.…”
Section: Discussionsupporting
confidence: 87%
“…demonstrated that Ab production is low and not hampering treatment responses to PEG‐IFN. Furthermore, these results are also supported by earlier studies showing no significant differences in overall percentage of sero‐conversion between responders and non‐responders. The differences in AST but not ALT levels found here are also in agreement with a recent report showing that rapid normalization of ALT by 4 weeks after treatment might be an independent significant predictive factor for SVR.…”
Section: Discussionsupporting
confidence: 87%
“…Anti-IFN NAbs were reported to be associated with a poor response of CH-C treated with IFN, particularly in patients treated with non-natural recombinant IFNs [29][30][31][32] . With regard to HCV-infected patients receiving rIFN-α, several previous studies have suggested that anti-IFN-α NAb were more frequently detected in the sera of non-responders than in that of responders [29][30][31][32] . Because of the difficulty in obtaining a SVR, Japanese HCV-infected patients with "1b/high" sometimes received multiple kinds of IFN therapy, and frequently develop anti-IFN-α NAbs.…”
Section: The Role Of Anti-ifn-α Neutralizing Antibodies In Ifn-α Treamentioning
confidence: 99%
“…Antibody formation due to the immunogenicity of recombinant human proteins in animal studies (Toon 1996) and against human recombinant IFNs used for a variety of indications (Antonelli & Dianzani 1999; Bertolotto et al 2004), including the use of recombinant human IFN‐α during the treatment of hepatitis C virus infection (Milella et al 1993 & 1995; Giannelli et al 1994; Antonelli 1995 & 1996; Haria & Benfield 1995; Bonino et al 1997; Hoffman et al . 1999) is well known, so our observations were not unexpected.…”
Section: Discussionmentioning
confidence: 99%